2022
DOI: 10.1115/1.4053314
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effects on Backward-Facing Step Flow of Ferrofluids

Abstract: Backward-facing step (BFS) flow is a benchmark case study in fluid mechanics. Its control by means of electromagnetic actuation has attracted great interest in recent years. This paper focuses on the effects of a uniform stationary magnetic field on the laminar ferrofluid BFS flows for the Reynolds number range 0.1=Re=400 and different expansion ratios. The coupled ferrohydrodynamic equations, including the microscopically derived magnetization equation, for a two-dimensional domain are solved numerically by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Yang et al [13] discovered that the corner vortex's normalized recirculation length rises nonlinearly with magnetic Reynolds number (Re m ) and Brownian Peclect number for ferrofluid flow over a backward-facing step in a magnetic field for Reynolds numbers 0.1-400. They found that for the case of Re m >> 1 and Re m << 1, the recirculation length tends to be a constant value.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [13] discovered that the corner vortex's normalized recirculation length rises nonlinearly with magnetic Reynolds number (Re m ) and Brownian Peclect number for ferrofluid flow over a backward-facing step in a magnetic field for Reynolds numbers 0.1-400. They found that for the case of Re m >> 1 and Re m << 1, the recirculation length tends to be a constant value.…”
Section: Introductionmentioning
confidence: 99%